SUPERVISION OF ELEMENTARY SCHOOL TEACHERS IN DEVELOPING IN-DEPTH LEARNING ASSESSMENTS - Wardani, Imas Srinana (LPM Universitas Pasundan, 2025)
Assessment is a crucial component of deep learning because it serves not only to assess learning outcomes but also to support students' thinking processes, conceptual understanding, and reflection. However, elementary school teachers still face various obstacles in developing assessments that align with deep learning principles. This community service activity aims to assist elementary school teachers in developing deep learning assessments at SDN Ketidur Mojokerto. The community service method uses a participatory approach through questionnaire-based needs analysis, assistance in developing assessment instruments, limited implementation, and reflection and evaluation. The questionnaire results indicate that most teachers have a good understanding of the concept of deep learning assessments, but still experience difficulties in developing instruments to assess learning processes and outcomes. Through the mentoring activity, teachers are able to develop authentic, task-based assessments and rubrics that assess students' deep understanding and thinking processes. This activity contributes to improving teachers' competency in designing applicable and contextual deep learning assessments in elementary schools.